John Michael Greer, The King in Orange: The Magical and Occult Roots of Political Power - Clifton, Chas (The pomegranate, 2021)
John Michael Greer, The King in Orange: The Magical and Occult Roots of Political Power (Rochester, Vt.: Inner Traditions, 2021). 202 pp. $16.99 (paper).